(untitled) (Journal of Global Accounting, 2023)
This study evaluates the determinants of audit quality disclosures of non-financial firms listed on the Nigerian Exchange group. Specifically, it intends to investigate the relationship between competence, audit tenure, audit size and the audit quality disclosure of selected non-financial firms listed on the Nigerian Exchange group. Adopting the ex-post-facto research design, a population of 116 non-financial firms listed on the Nigerian Exchange group as at March 1, 2021 were framed for the sample selection for the years 2012 to 2021. Thus, the content analysis approach was deployed for the extract of data from the annual reports of the sampled firms even as the Pearson correlation and Panel Least Square Regression statistical tools were used to test the hypotheses formulated in the study. The findings of the study show that competence and audit tenure have a positive and significant relationship with audit quality disclosure while audit size portrayed a significant but negative relationship with audit quality disclosure. Based on these findings, the study concludes that relevant stakeholders such as Management, Shareholders, Auditors and Investors will place high premium on competence as core factor leading to high audit quality disclosure. Shareholders will become very willing and interested in retaining and extending the tenure of their external Auditors even as Investors and other stakeholders will have more confidence on the credibility of the audited reports. To this end, the size of an audit firm may no longer be relevant in the selection of an External Auditor by the client. The study therefore recommends that. the audit firms and the organizations that require the services of an Auditor should ensure that the requisite audit skills of their staff are up to date to match the contemporary dynamics in the corporate environment of interest. Also, the audit tenure of Auditors should at least be three years and at most ten years in line with corporate governance best practice. Finally, corporate organizations should as much as possible strive to engage External Auditors with the requisite state of the art competencies irrespective of whether the firm is small, medium and large in size